Pengaruh Citra Merek, Kualitas Produk, dan Harga Terhadap Keputusan Pembelian Paket Internet Telkomsel - Riska Nindia Sari; Anwar Hakim Darajat (Universitas Islam Balitar, 2021)
This study aimed to determine the effect of brand image, product quality, and price on the decision to purchase Telkomsel internet packages among students of The Faculty of Social and Political Sciences, Islamic University of Balitar partially and smultaneously. This research used quantitative research with descriptive method. There were three variables, namely brand image, product and price and the independent variable is the purchase decision variable. The sampling technique used saturated sampling with a population of consumers who bought Telkomsel cards as many as 96 students. The data collection technique used a questionnaire which tested using SPSS 18.0 application with multiple linier regression analysis techniques. Based on the results of the study, it shows that (1) brand image was effected significantly on the decisions of purchasing Telkomsel internet packages partially, (2) product quality was effected significantly on the decisions of purchasing Telkomsel internet packages partially, (3) price was effected significantly on the purchasing decisions for Telkomsel internet packages partially, (4) brand image, product quality and price were effected significantly on the decision of purchasing Telkomsel internet packages simultaneously.